The relation between oxygen saturation level and retionopathy of prematurity - Mohammad Gharavi Fard (Reviews in Clinical Medicine, 2016)
Introduction: Oxygen therapy used for preterm infant disease might be associated with oxygen toxicity or oxidative stress. The exact oxygen concentration to control and maintain the arterial oxygen saturation balance is not certainly clear. We aimed to compare the efficacy of higher or lower oxygen saturations on the development of severe retinopathy of prematurity which is a major cause of blindness in preterm neonates. Methods: PubMed was searched for obtaining the relevant articles. A total of seven articles were included after studying the titles, abstracts, and the full text of retrieved articles at initial search. Inclusion criteria were all the English language human clinical randomized controlled trials with no time limitation, which studied the efficacy of low versus high oxygen saturation measured by pulse oximetry in preterm infants.Result: It can be suggested that lower limits of oxygen saturations have higher efficacy at postmesetural age of ≤28 weeks in preterm neonates. This relation has been demonstrated in five large clinical trials including three Boost trials, COT, and Support.Discussion: Applying higher concentrations of oxygen supplementations at mesentural age ≥32 weeks reduced the development of retinopathy of prematurity. Lower concentrations of oxygen saturation decreased the incidence and the development of retinopathy of prematurity in preterm neonates while applied soon after the birth.Conclusions: Targeting levels of oxygen saturation in the low or high range should be performed cautiously with attention to the postmesentural age in preterm infants at the time of starting the procedures.